Management Implementation Project Strengthening the Profile of Pancasila Students (P5) at SMAS Muhammadiyah Toboali - Thoriq, Alfan; Mahmudah, Fitri Nur (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This research aims to find out how the management of SMAS Muhammadiyah Toboali is implementing the project of Strengthening the Profile of Pancasila Students (P5). Qualitative research with a descriptive approach is the research design used in this article. Five participants were involved in this research: the school principal, the curriculum representative, the P5 coordinator, the P5 facilitator and the students of Class X. Data collection techniques used were interviews and documentary studies.  This research uses interactive data analysis. Data analysis techniques used models Miles and Huberman with the help of software atlas.ti version 8 by creating word codes to facilitate the presentation of the data obtained. Research results: Indicators found from P5 management planning for SMA in the planning component consist of principal leadership, curriculum development, school policies, local wisdom, determining schedules and modules, determining coordinators, determining facilitators, and determining themes. The indicators found from the organization of P5 management for SMA in the organizing component consist of freedom to learn, teacher willingness, coordination, similarity of perception, concern, mutual agreement, division of tasks, and socialization. The indicators found from the implementation of P5 management for SMA in the implementation component consist of student involvement, habituation, task descriptions, innovation, social media, work titles, collaboration, adaptation, partnership, and harmony. The indicators found from evaluating P5 management for SMA in the evaluation component consist of: follow-up, based on competency, level of achievement, sustainability, independence, digital era, and school culture.